Application of Starter Solution Increased Yields of Chili Pepper (Capsicum annuum L.) - Anas Dinurrohman Susila; Chin-Hua Ma; Manuel Celiz Palada (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
Chili pepper (Capsicum annuum L.) was grown with polyethylene mulched on Inceptisol soil with low pH (5.5), low organic-C (1.54%), very low total N (0.12%), low K content (0.29 me (100 g)-1), but very high soil P2O5 concentration (19.2 ppm) to evaluate the best crop management practices with starter solution. Seven starter solution combinations (1 = No Starter Solution + No CM + No SI, 2 = CM + SSVC, 3 = CM + SSG, 4 = SI + SSVC, 5 = SI + SSG, 6 = SI + CM+ SSVC, and 7 = SI + CM + SSG) were arranged in a randomized completely block design with four replications. Whereas CM = cow manure, SSVC = organic starter solution, SSG = inorganic starter solution, and SI=standard inorganic fertilizer. The results showed that inorganic, as well as organic, starter solution increased chili pepper growth and yield in less fertile soil. The highest marketable yield was obtained with application of standard inorganic (SI) + cow manure (CM) + inorganic starter solution (SSG). Inorganic starter solution application resulted in a better plant growth than organic starter solution, being evident at 1 week until 7 weeks after transplanting. However, inorganic starter solution did not signifi cantly increase total marketable yields. Application of cow manure, standard inorganic fertilizer, or addition of organic starter solution reduced total unmarketable yield, improved fruit qualities and increased marketable yield